FAKTOR YANG BERHUBUNGAN DENGAN KELELAHAN KERJA SUBYEKTIF PADA PERAWAT DI RSUD DR. MOHAMAD SOEWANDHIE SURABAYA - Dita Perwitasari; Abdul Rohim Tualeka (Universitas Airlangga, 2017)
Fatigue is a subjective feeling that different for everyone, which leads to loss of efficiency, decreases work capacity, health problem and the body's ability to survive resulting in work accident. The purpose of this research was examining the factors associated with subjective work fatigue on nurses working in dr. Mohamad Soewandhie hospital in Surabaya.This research was an observational study with cross sectional design. The respondents were nurses of emergency, outpatient, and inpatient units in dr.Mohamad Soewandhie hospital. The variables were individual factors were consisting of age, years of working life, nutritional status, gender, and occupational factors were consisting of the workload and the monotony condition of work toward work fatigue. Spearman correlation test was using to test the relationship of each factors, except the relationship of gender and the monotony condition were using Mann-Whitney.The results showed that the most of the respondentss were 25-30 years old, female, 1-10 years of working life, had better nutritional status, had a moderate heavy workload and felt the monotony condition in her work. The result of fatigue measurement used the checklist which indicated that the most of the respondents experienced no relationship between age, gender, years of working life, workload, and the monotony condition the results also proved the existence of a relationship between nutritional status with p=0,00. It could be concluded that the nutritional status of nurse in dr.Mohamad Soewandhie hospital had a risk of causing fatigue. Keywords: Individual factors, occupational factors, and work fatigue